Woven Identities: Socioeconomic Change, Women’s Agency, and the Making of a Heritage Art in Jølster, Norway - Sallie Anna Steiner (Journal of Ethnology and Folkloristics)
This article focuses on the recent history and contemporary practice of a kind of traditional tapestry weaving known as smettvev in the rural county of Jølster in mountainous western Norway. Jølster has a rich fibre arts tradition and a rapidly changing society and economy, which make it an exemplary study in material culture as its fibre arts transform to accommodate these changes. This article draws on ethnographic research and interviews with representative practitioners and community members to examine how conceptions about producer and audience identity and the role of this art form in everyday life have evolved in light of changing context. The article furthermore discusses the ways in which the forms and motifs associated with smettvev are being re-appropriated by local contemporary artists working in other mediums, as well as by individuals and institutions who see smettvev as a symbol of local identity and heritage.